2018
DOI: 10.1016/j.jhsa.2018.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Use After Upper Extremity Surgery

Abstract: Ever since the institution of pain as the fifth vital sign, there has been a rising opioid epidemic in the United States, with Americans now consuming 80% of the global opioid supply while representing only 5% of the world's population. Surgeons are tasked with the duty of both managing patients' pain in the perioperative period and following responsible prescribing behaviors. Several articles have been published with the goal of evaluating opioid use after upper extremity surgery, risk factors for opioid misu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
60
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 21 publications
2
60
1
Order By: Relevance
“…maximum pain score before study drugminimum pain score before rescue medication treatment) was 3 (2,5) in the ibuprofen group, compared to -0.5 (-2, 1.25) in the placebo group (p<0.001). The patients' global assessment of pain relief also favored ibuprofen with 16 of 19 subjects who received ibuprofen rating their pain as "much better" or "very much better" after study drug treatment, compared to 0 of 10 subjects who received placebo (p<0.0001; Fisher exact test).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…maximum pain score before study drugminimum pain score before rescue medication treatment) was 3 (2,5) in the ibuprofen group, compared to -0.5 (-2, 1.25) in the placebo group (p<0.001). The patients' global assessment of pain relief also favored ibuprofen with 16 of 19 subjects who received ibuprofen rating their pain as "much better" or "very much better" after study drug treatment, compared to 0 of 10 subjects who received placebo (p<0.0001; Fisher exact test).…”
Section: Discussionmentioning
confidence: 91%
“…Opioid analgesics are an important component of post-operative pain management in many patients. However, over-prescription of opioids for surgical pain, typically 2-5 times more than patients actually use, has contributed to the opioid epidemic [1,2]. Thus, there is a need to consider alternative therapeutic options for those patients, whose pain can be appropriately managed with non-addictive analgesics, including nonsteroidal anti-inflammatory drugs (NSAIDs).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is especially relevant as 28 to 72% of patients undergoing hand and upper extremity surgery do not fill prescriptions for postoperative opioids. 14,16,18 This suggests that continued opioid use following hand and upper extremity surgery is concentrated to a subset of the patient population. Use of opioids preoperatively is likely a key characteristic for the subset of patients at high risk for developing prolonged postoperative opioid use and dependence following FCA or PRC.…”
Section: Discussionmentioning
confidence: 99%
“…10,13 Recent studies have investigated opioid use following hand and upper extremity surgery, reporting that surgeons typically prescribe substantially more opioid pills (two to five times more) than necessary. [13][14][15][16][17][18][19] Johnson et al examined 77,573 opioid-naive patients undergoing common hand and upper extremity procedures and found that of the 77% of patients who filled an opioid prescription postoperatively, 13% continued to fill those prescriptions beyond 90 days after the index procedure. Risk factors for prolonged postoperative opioid use in this study included younger age, female, higher number of medical comorbidities, and mental health diagnoses, among others.…”
Section: Introductionmentioning
confidence: 99%
“…epidemic in the United States. 1,2 Thus, there is a need to consider alternative therapeutic options for those patients whose pain can be appropriately managed with nonaddictive analgesics, including nonsteroidal anti-inflammatory drugs (NSAIDs).…”
mentioning
confidence: 99%